Bab E-Syifa’ clinic administration system. - Abu Bakar, Mohd Danel; Othman, Roslina (IIUM Press, 2011)
Bab E-Shifa main focus is to serve customers \vith optimum services so it meets customers' satisfaction. However, during the operation, sometimes Dr. Saeed faces lot of problems that may cause negative effects to his business management quality. The major problem is in managing patient's data. The patient's data management is currently done manually, which is file base system. File base system is time consuming and inefficient. Therefore. database system is highly required in this clinic so patient's data would be managed efficiently and effectively